Non-Compaction Cardiomyopathy and Multiple Sclerosis: Associated or Independent Diseases? A Case Report - Muñoz Moreno, Juan Manuel; Holguin Palacios, Carlos; Lobato Jeri, Carlos; Reyes Villanes, Sebastian; Peralta Ramos, Wilson; Reyes Rocha, Miguel (Frontiers in Cardiovascular Medicine, 2022)
Non-compaction cardiomyopathy (NCCM) is associated with neuromuscular disorders; however, there has been little investigation on its association with other neurological diseases, such as multiple sclerosis. We present the case of a 46-year-old woman with a history of multiple sclerosis who developed heart failure and was diagnosed with non-compaction cardiomyopathy.